2001
DOI: 10.1523/jneurosci.21-19-07630.2001
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Inner Ear Maturation and Neuronal Loss in PostnatalIgf-1-Deficient Mice

Abstract: Insulin-like growth factor-1 (IGF-1) has been shown to play a key role during embryonic and postnatal development of the CNS, but its effect on a sensory organ has not been studied in vivo. Therefore, we examined cochlear growth, differentiation, and maturation in Igf-1 gene knock-out mice at postnatal days 5 (P5), P8, and P20 by using stereological methods and immunohistochemistry. Mutant mice showed reduction in size of the cochlea and cochlear ganglion. An immature tectorial membrane and a significant decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
159
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(169 citation statements)
references
References 71 publications
7
159
2
1
Order By: Relevance
“…The delayed response to acoustic stimuli along the auditory pathway indicates the contribution of the CNS to the hearing loss in IGF-I deficiency (81). At a cellular level, a significant decrease in number and size of auditory neurons, increased apoptosis of cochlear neurons, a significant reduced volume of the cochlea and cochlear ganglion can result in abnormal differentiation and maturation of the cochlear ganglion cells and abnormal innervation of the sensory cells in the organ of Corti (82).…”
Section: Hearingmentioning
confidence: 99%
“…The delayed response to acoustic stimuli along the auditory pathway indicates the contribution of the CNS to the hearing loss in IGF-I deficiency (81). At a cellular level, a significant decrease in number and size of auditory neurons, increased apoptosis of cochlear neurons, a significant reduced volume of the cochlea and cochlear ganglion can result in abnormal differentiation and maturation of the cochlear ganglion cells and abnormal innervation of the sensory cells in the organ of Corti (82).…”
Section: Hearingmentioning
confidence: 99%
“…This could be due to the fact that stress affects various parts of CANS differently (11). It was highlighted in one study that the effect of stress on neuronal atrophy of inferior colliculus (IC) is much more than on the hippocampus (10). It was also revealed that after stress is induced to rats, expression of genes related to glucocorticoid receptor (GR) and Hif-1 (hypoxia-inducible factors) mainly occurs in IC and cochlear nuclei (11).…”
Section: Discussionmentioning
confidence: 99%
“…It was also revealed that after stress is induced to rats, expression of genes related to glucocorticoid receptor (GR) and Hif-1 (hypoxia-inducible factors) mainly occurs in IC and cochlear nuclei (11). This in indicative of the fact that unlike more peripheral structures, central parts of the afferent auditory pathway are more affected by prenatal stress (10). Since waves II and IV in rats are respectively generated by cochlear nuclei and IC (20), their increased latency time could be caused by greater impact of prenatal stress on their generators.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations